2021
DOI: 10.3390/en14165165
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Carbon Emissions and Energy Implications of High Penetration of Photovoltaics and Electric Vehicles in California

Abstract: California has set two ambitious targets aimed at achieving a high level of decarbonization in the coming decades, namely (i) to generate 60% and 100% of its electricity using renewable energy (RE) technologies, respectively, by 2030 and by 2045, and (ii) introducing at least 5 million zero emission vehicles (ZEVs) by 2030, as a first step towards all new vehicles being ZEVs by 2035. In addition, in California, photovoltaics (PVs) coupled with lithium-ion battery (LIB) storage and battery electric vehicles (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Another recent analysis focusing on California and based on a detailed 1 h-resolution power dispatch model informed by actual historical demand and generation data found that a projected 80% RE generation mix relying heavily on PV would be capable of meeting the domestic demand profile while only requiring 6 h of storage capacity [65]. A follow-up study further calculated that a similar amount of storage (in terms of duration) would suffice while also meeting the additional demand created by 10 million EVs on California roads [141].…”
Section: Statements In the Seibert-rees (S-r) Paper And Counter-argumentsmentioning
confidence: 99%
“…Another recent analysis focusing on California and based on a detailed 1 h-resolution power dispatch model informed by actual historical demand and generation data found that a projected 80% RE generation mix relying heavily on PV would be capable of meeting the domestic demand profile while only requiring 6 h of storage capacity [65]. A follow-up study further calculated that a similar amount of storage (in terms of duration) would suffice while also meeting the additional demand created by 10 million EVs on California roads [141].…”
Section: Statements In the Seibert-rees (S-r) Paper And Counter-argumentsmentioning
confidence: 99%
“…Due to concerns about greenhouse gas emissions and global warming, governments worldwide are actively promoting policies aimed at achieving net-zero emissions, not only in the energy sector but also in transportation [1,2]. Among these initiatives, electric vehicles have garnered significant attention.…”
Section: Introductionmentioning
confidence: 99%